Conservation of Pyrus L. biodiversity in Central Kazakhstan (Eurasian Journal of Ecology, 2016)
As a result of cooperation of Zhezkazgan botanical garden with leading centres of science of Kazakhstan and Russia the collection of modern pear cultivars is created in Central Kazakhstan that promoted the increase of biodiversity of cultural flora of region. New cultivars have high adaptable abilities, are capable to resist to adverse climatic conditionsof arid zone of Central Kazakhstan and considerably surpass cultivars of old assortment in a number of economicvaluable signs. These cultivars have fruits of different terms of maturing: ′Veselinka′, ′Chizhovskaya′  summer; ′Velesa′ and ′Barnaulskaya krupnaya′  early autumn; ′Vidnaya′ and ′Zolotinka′  autumn; ′Povislaya′ and ′Pamyatnaya′  lateautumn; ′Muratovskaya′ and ′Vidnaya′ differ dessert taste of fruits. ′Malinovka′ and ′Vtselinka′ possess very high winterhardiness, regular fructification.
Keywords: biodiversity; cultivar; pear; winter hardiness; Central Kazakhstan.